Neokolonialisme Modern: Kemitraan Angola-China dalam Kerangka Belt and Road Initiative - Zharfan Surya Nauvally (Yayasan Literasi Sains Indonesia, 2025)
This paper examines the modern neocolonial relationship between Angola and China in the context of the Belt and Road Initiative (BRI). Since the 1960s, China has been involved in assisting Angola, especially during its struggle against Portuguese colonialism. Formal relations began in 1983, with China providing military and economic support, including large loans for post-war infrastructure recovery. The paper uses concepts of neocolonialism and world system theory to describe Angola’s dependence on China. In this context, Angola experiences exploitation of its natural resources by Chinese companies that profit greatly, while local communities often do not receive equal benefits. The BRI, launched in 2013, aims to improve infrastructure in developing countries but has also become a tool for China to strengthen its influence in Angola. This article analyzes the impact of China’s 46 billion in loans, focusing on the energy and transportation sectors. Angola’s dependence on these loans poses a debt risk that could lead to “debt trap diplomacy.” Despite efforts to diversify investments into other social sectors, challenges remain in ensuring that these projects can fuel sustainable economic growth without exacerbating dependence on China.